The Effect of Low-Dose Methotrexate and Corticosteroids Treatment on Bone Mineral Density in Patients with Early Rheumatoid Arthritis - Original Investigation - Figen Gökoğlu; Mukaddes Yılmaz; Müyesser Okumuş; Esma Ceceli; Rezan Yorgancıoğlu (Galenos Yayinevi, 2005)
The aim of this study was to determine the difference between bone mineral density of rheumatoid arthritis patients on low dose methotrexate matched rheumatoid arthritis on low dose methotrexate plus low dose corticosteroids therapy. Fifty patients with early rheumatoid arthritis were randomised to 7,5 -10 mg/week of methotrexate and 7,5-10 mg/week of methotrexate plus 7,5-10 mg/day of corticosteroids. Bone mineral density of the lumbar spine, femoral neck, and trochanter was measured using dual-energy X-ray absorptiometry. Functional impairment was evaluated by the Health Assessment Questionnaire. There was no statistically difference between the bone mineral density values at the lumbar spine and at the femoral neck and HAQ scores for two groups (p>0,05). There was also no significant change in the biochemical parameters of both groups. Our results suggest that low dose methotrexate plus low dose corticosteroids does not have additional negative effect on bone mineral density, at either cortical or trabecular sites. (Osteoporoz Dünyasından 2005; 4: 151-154)